Analysis on basic health unit constructions in Brazil - Campos, Mônica Sinésio de Lima Ferro e; Tibúrcio Silva, César Augusto (Revista Gestão & Saúde, 2021)
The work deals with the analysis of expenses with Basic Health Units (UBS) in Brazil from 2010 to 2018. It aims to verify the relationship between the construction of BHU with the source of the Executive's own or by parliamentary amendment. The numerical data were used together with descriptive statistics to examine the number of proposals for UBS construction, the amount paid, and whether they were successful in their building, or failure, with their cancellation. The relationship with the population, the area, the MHDI, and the GDP per capita of the municipality where the work was located was also analyzed. When exploring the type of resource allocated, the effectiveness of UBS implemented with resources from the government's program is verified in comparison to proposals with resources via parliamentary amendment, with a success rate of 76.8% for own resources of the Ministry of Health and 57.4% for buildings completed with funds from parliamentary amendments. It was also possible to observe the effect of the economic crisis on the success rate.